CROWN ROOTLESS1 binds DNA with a relaxed specificity and activates OsROP and OsbHLH044 genes involved in crown root formation in rice - Gonin, Mathieu; Jeong, Kwanho; Coudert, Yoan; Lavarenne, Jeremy; Hoang, Giang Thi; Bes, Martine; To, Huong Thi Mai; Thiaw, Marie-Rose Ndella; Do, Toan Van; Moukouanga, Daniel; Guyomarc'h, Soazig; Bellande, Kevin; et al. (The Plant journal, 2022)
In cereals, the root system is mainly composed of post-embryonic shoot-borne roots, named crown roots. The CROWN ROOTLESS1 (CRL1) transcription factor, belonging to the ASYMMETRIC LEAVES2-LIKE/LATERAL ORGAN BOUNDARIES DOMAIN (ASL/LBD) family, is a key regulator of crown root initiation in rice (Oryza sativa). Here, we show that CRL1 can bind, both in vitro and in vivo, not only the LBD-box, a DNA sequence recognized by several ASL/LBD transcription factors, but also another not previously identified DNA motif that was named CRL1-box. Using rice protoplast transient transactivation assays and a set of previously identified CRL1-regulated genes, we confirm that CRL1 transactivates these genes if they possess at least a CRL1-box or an LBD-box in their promoters. In planta, ChIP-qPCR experiments targeting two of these genes that include both a CRL1- and an LBD-box in their promoter show that CRL1 binds preferentially to the LBD-box in these promoter contexts. CRISPR/Cas9-targeted mutation of these two CRL1-regulated genes, which encode a plant Rho GTPase (OsROP) and a basic helix-loop-helix transcription factor (OsbHLH044), show that both promote crown root development. Finally, we show that OsbHLH044 represses a regulatory module, uncovering how CRL1 regulates specific processes during crown root formation.
Keywords: Oryza sativa; gene regulatory network; transkripční faktory; rice; rýže (rod); Plant Proteins; Oryza; DNA; crown root; Transcription Factors; ASL/LBD transcription factor; rostlinné proteiny; DNA binding domain; CRL1; Plant Roots; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; development; kořeny rostlin